Pengaruh Kepemilikan Manajerial, Kepemilikan Institusional, Arus Kas Bebas, dan Leverage Terhadap Kebijakan Dividen - Shintya Nurhanifah Firdaus; Mujino Mujino; Risal Rinofah (Jurnal Ilmiah Manajemen dan Bisnis, 2020)
The study aims at testing thee effect managerial ownership, institutional ownership, free cash flow, and leverage on dividend policy of manufacturing companies in other industry sector and consumer goods industry sector on the Indonesia Stock Exchange. The study collected from annual report the Indonesia Stock Exchange consisting of 13 companies. The data were collected from annual report from five consecutive years (2014 – 2018). The finding indicates that the variable that have a significant effect on dividend policy are free cash flow and leverage. While the variable of managerial ownership and institutional ownership do not significantly affect dividend policy.